ANALISIS PENGGUNAAN ABU SEKAM PADI SEBAGAI BAHAN TAMBAH DALAM CAMPURAN PAVING BLOCK TERHADAP KUAT TEKAN DAN POROSITAS - Ananda Sitorus, Eka Rizky; Irwansyah, Muhammad; Zahar, Intan (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
Paving blocks are one of the construction materials used as surface coverings, particularly in pedestrian areas, yards, and local roads. In this study, paving blocks were produced by utilizing rice husk ash (RHA) as an additive in the mixture. The use of rice husk ash was chosen due to its high silica content and its potential as an environmentally friendly pozzolanic material. The objective of this research is to determine the compressive strength of paving blocks with variations in rice husk ash content. The mixture variations used were 0%, 6%, and 12% of the total cement weight, with thicknesses of 6 cm and 8 cm, respectively. The compressive strength and porosity tests were conducted at 28 days in accordance with SNI 03-0691-1996. The results showed that the best compressive strength and porosity were obtained in the 0% RHA mixture, reaching 10.99 MPa, compared to the 6% and 12% RHA mixtures. The addition of rice husk ash tended to decrease the compressive strength of the paving blocks due to the increase in porosity, although at certain variations it still met the quality category D according to the SNI standard.